2021
DOI: 10.3390/diagnostics11081324
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of Saliva and Plaque in Children According to Age and Dental Caries Experience

Abstract: Dental caries are one of the chronic diseases caused by organic acids made from oral microbes. However, there was a lack of knowledge about the oral microbiome of Korean children. The aim of this study was to analyze the metagenome data of the oral microbiome obtained from Korean children and to discover bacteria highly related to dental caries with machine learning models. Saliva and plaque samples from 120 Korean children aged below 12 years were collected. Bacterial composition was identified using Illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 64 publications
4
20
0
Order By: Relevance
“…Regarding genus classi cation, Metastat analysis revealed signi cant between-group differences in the abundance of Neisseria, Lautropia, Lactobacillus, Porphyromonas, and Aggregatibacter (p < 0.05). A previous study reported that Neisseria was more abundant in CF children and could be a diagnostic biomarker [44], which is consistent with our ndings. Additionally, a previous study found that Veillonella was more abundant in childhood caries and that its co-aggregation and adhesion with Streptococcus spp.…”
Section: Microbiomesupporting
confidence: 93%
“…Regarding genus classi cation, Metastat analysis revealed signi cant between-group differences in the abundance of Neisseria, Lautropia, Lactobacillus, Porphyromonas, and Aggregatibacter (p < 0.05). A previous study reported that Neisseria was more abundant in CF children and could be a diagnostic biomarker [44], which is consistent with our ndings. Additionally, a previous study found that Veillonella was more abundant in childhood caries and that its co-aggregation and adhesion with Streptococcus spp.…”
Section: Microbiomesupporting
confidence: 93%
“…The introduction of high-throughput 16S rRNA sequencing has provided new insights into the compositions and structures of microbial communities ( Yang et al., 2012 ). At present, giant panda oral microbes still need to be explored, in order to better classify and identify microorganisms, we have selected the more reported V3 and V4 variable regions which yield the highest accuracies of phylogenetic assignment and Illumina mature system in our study ( Xu et al., 2018 ; Lee et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since periodontitis is the result of a disturbed microbial homoeostasis, 163 an improvement of personal oral hygiene, coupled with professional biofilm and calculus removal followed by an individually tailored supportive therapy are the key parts of successful periodontal therapy 211 . While mechanical root debridement leads to a microbiome comparable to that of periodontally healthy subjects, 212 personal oral hygiene and instrumentation decrease inflammatory mediators in the oral cavity 213 . Dental therapy in mild AD improved periodontal indices and quality of life 214 .…”
Section: Discussionmentioning
confidence: 99%